2021
DOI: 10.21053/ceo.2020.00584
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Hypotensive Agents on Intraoperative Bleeding and Recovery Following General Anesthesia for Nasal Surgery: A Network Meta-Analysis

Abstract: Objectives. A systematic review of the literature was conducted to evaluate hypotensive agents in terms of their adverse effects and associations with perioperative morbidity in patients undergoing nasal surgery. Methods. Two authors independently searched databases (Medline, Scopus, and Cochrane databases) up to February 2020 for randomized controlled trials comparing the perioperative administration of a hypotensive agent with a placebo or other agent. The outcomes of interest for this analysis were intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…The data from the included studies were extracted using standardized forms. 8,9 The primary outcomes of the meta-analysis were the odds ratios (ORs; comparison of outcomes between two groups) for the recurrence of inverted papilloma, facial or gingival numbness, nasal bleeding, and periorbital swelling during follow-up (prelacrimal recess approach vs. conventional surgery [EMM, endoscopic surgery, and/or the Caldwell-Luc operation]). 1,3,[10][11][12][13][14] Additionally, the incidence rates of recurrence and postoperative morbidities (postoperative facial or gingival numbness and alar collapse) after prelacrimal recess approach were assessed as secondary outcomes.…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…The data from the included studies were extracted using standardized forms. 8,9 The primary outcomes of the meta-analysis were the odds ratios (ORs; comparison of outcomes between two groups) for the recurrence of inverted papilloma, facial or gingival numbness, nasal bleeding, and periorbital swelling during follow-up (prelacrimal recess approach vs. conventional surgery [EMM, endoscopic surgery, and/or the Caldwell-Luc operation]). 1,3,[10][11][12][13][14] Additionally, the incidence rates of recurrence and postoperative morbidities (postoperative facial or gingival numbness and alar collapse) after prelacrimal recess approach were assessed as secondary outcomes.…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Even a small bleeding in the operation area in the ear, nose, or throat affects the appearance of the operation area [17]. Although epinephrine is used to reduce pre-surgical bleeding, increases in arterial pressure can cause increase surgical bleeding [18].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] compared dexmedetomidine and magnesium sulphate and found that better operating condition was provided by dexmedetomidine but with more hypotension and bradycardia like our study. Kim et al .,[ 19 ] in a meta-analysis of randomised controlled trials comparing the perioperative administration of hypotensive agents, found dexmedetomidine to be a superior agent. They also concluded that systemic use of dexmedetomidine reduces intraoperative bleeding and operating time, provides relatively stable haemodynamics by alleviating stress response and reduces the fentanyl requirement significantly.…”
Section: Discussionmentioning
confidence: 99%